SERAGAM OLAHRAGA PEREMPUAN DALAM PERSPEKTIF HUKUM ISLAM DAN TEORI SEKSISME - Muhammad Rosyid Ridho; Uswatul Khasanah; Martha Eri Safira (IJouGS: Indonesian Journal of Gender Studies, 2021)
Women's participation in sports matches has increased every year, not least in the Tokyo 2020 Olympic Games. In the worldof sports, it does not escape some of the controversies that surroundit. Kontroversion is meant here is in terms of the uniforms that athletes wear in competing. One of them was a gymnastics athlete from Germany as well as a Norwegian handball team who were subject to penalties. The case shows that there is discrimination against women through regulations in the use of uniforms.. Looking at this, the authors were interested in researching and analyzing how women's sportswear is viewed from Islamic law and sexism theory, how it impacts and the solution of both theories. The results of this study can be concluded that if it is reviewed from the point of view of hifz al-'ird, the awarding of fines to the athlete is considered unable to meet the protection of honor, especially in the care of dignity and dignity of women As for the actions of female athletes who refuse to wear sports uniforms have been in harmony with the concept of hifz al-'ird. In the view of hifz al-'ird, the uniform worn by athletes must be a uniform that can protect the honor of the athletes while when viewed from the glasses of sexism, it is very clear that there are uniform rules that make women more objects of sexuality in sports.. Supposedly, auniform of a female athlete should be based on the comfort of the athlete who will wear it at sporting events. Keyword: Uniform; hifz al-'ird; sexism